2015
DOI: 10.1097/ccm.0000000000001279
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia Within Two Postoperative Days Is an Independent Risk Factor for Acute Kidney Injury Following Living Donor Liver Transplantation

Abstract: Early postoperative hypoalbuminemia is an independent risk factor for acute kidney injury, and postoperative acute kidney injury is related to postoperative ICU stay and overall mortality after living donor liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 35 publications
8
74
0
Order By: Relevance
“…Furthermore, ICU ( P = 0.006) and hospital ( P < 0.001) stays were prolonged in the low albumin group and overall mortality was also higher ( P = 0.02), making this one of the few studies retained from our literature review to report data associating serum albumin level with mortality. The findings of Sang et al[46] are consistent with an earlier, smaller retrospective study by Chen et al[44] in which multivariable analysis of 118 matched pairs of liver transplantation patients with/without postoperative renal injury demonstrated that preoperative hypoalbuminemia (≤ 3.5 g/dL) was strongly predictive of AKI within the first week after surgery. Similarly, Park et al[47] also identified by multivariate analysis that preoperative serum albumin < 3.5 g/dL was an independent, modifiable risk factor for AKI (RIFLE classification) in patients ( n = 538) undergoing LDLT.…”
Section: Transplant Surgerysupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, ICU ( P = 0.006) and hospital ( P < 0.001) stays were prolonged in the low albumin group and overall mortality was also higher ( P = 0.02), making this one of the few studies retained from our literature review to report data associating serum albumin level with mortality. The findings of Sang et al[46] are consistent with an earlier, smaller retrospective study by Chen et al[44] in which multivariable analysis of 118 matched pairs of liver transplantation patients with/without postoperative renal injury demonstrated that preoperative hypoalbuminemia (≤ 3.5 g/dL) was strongly predictive of AKI within the first week after surgery. Similarly, Park et al[47] also identified by multivariate analysis that preoperative serum albumin < 3.5 g/dL was an independent, modifiable risk factor for AKI (RIFLE classification) in patients ( n = 538) undergoing LDLT.…”
Section: Transplant Surgerysupporting
confidence: 78%
“…The largest of the three retrospective, observational studies assessing hypoalbuminemia in liver transplantation was a propensity score analysis of 998 consecutive living donor liver transplantation (LDLT) patients in a single center[46]. This analysis aimed to ascertain the influence of early postoperative serum albumin level on subsequent development of AKI.…”
Section: Transplant Surgerymentioning
confidence: 99%
“…Hypoalbuminemia is a predictor of mortality in patients with various illnesses [37][38][39][40][41]. Our study was the first to suggest the association between hypoalbuminemia and the mortality of IPFD.…”
Section: Discussionmentioning
confidence: 73%
“…Baseline characteristics included age, sex, body mass index, American Society of Anesthesiologists (ASA) grade, comorbidities, and surgical indication. Laboratory data included hemoglobin, preoperative CRP and albumin, CRP on POD 3 [7], and albumin on POD 3 [13]. Intraoperative data included operation time, type of surgery, surgical approach (open vs laparoscopy), stoma creation, intraoperative blood transfusion, and estimated blood loss during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical site complications included superficial incisional, deep incisional, or organ/space SSIs. For evaluation, CAR was defined as (CRP level on POD 3)/(ALB level on POD 3) [1, 13, 15]. The CAR cutoff values were determined using receiver operating characteristic (ROC) curve analysis [11].…”
Section: Methodsmentioning
confidence: 99%